Exogenous Coronavirus Interacts With Endogenous Retrotransposon in Human Cells - Yin, Ying; Liu, Xiao-zhao; He, Ximiao; Zhou, Li-quan (Frontiers in Cellular and Infection Microbiology, 2021)
There is an increased global outbreak of diseases caused by coronaviruses affecting respiratory tracts of birds and mammals. Recent dangerous coronaviruses are MERS-CoV, SARS-CoV and SARS-CoV-2, causing respiratory illness and even failure of several organs. However, profound impact of coronavirus on host cells remains elusive. In this study, we analyzed transcriptome of MERS-CoV, SARS-CoV and SARS-CoV-2 infected human lung-derived cells, and observed that infection of these coronaviruses all induced increase of retrotransposon expression with upregulation of TET genes. Upregulation of retrotransposon was also observed in SARS-CoV-2 infected human intestinal organoids. Retrotransposon upregulation may lead to increased genome instability and enhanced expression of genes with readthrough from retrotransposons. Therefore, people with higher basal level of retrotransposon such as cancer patients and aged people may have increased risk of symptomatic infection. Additionally, we show evidence supporting long-term epigenetic inheritance of retrotransposon upregulation. We also observed chimeric transcripts of retrotransposon and SARS-CoV-2 RNA for potential human genome invasion of viral fragments, with the front and the rear part of SARS-CoV-2 genome being easier to form chimeric RNA. Thus, we suggest that primers and probes for nucleic acid detection should be designed in the middle of virus genome to identify live virus with higher probability. In summary, we propose our hypothesis that coronavirus invades human cells and interacts with retrotransposon, eliciting more severe symptoms in patients with underlying diseases. In the treatment of patients with coronavirus infection, it may be necessary to pay more attention to the potential harm contributed by retrotransposon dysregulation.